Transition risk uncertainty and robust optimal monetary policy - Alexander Dück; Anh H. Le (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
Climate change has become one of the most prominent concerns globally. In this paper, we study the transition risk of greenhouse gas emission reduction in structural environmental-macroeconomic DSGE models. First, we analyze the uncertainty in model prediction on the effect of unanticipated and pre-announced carbon price increases. Second, we conduct optimal model-robust policy in different settings. We find that reducing emissions by 40% causes 0.7% - 4% output loss with 2% on average. Pre-announcement of carbon prices affects the inflation dynamics significantly. The central bank should react slightly less to inflation and output growth during the transition risk. With optimal carbon price designs, it should react even less to inflation, and more to output growth.
Keywords: Q58; E32; Q54; C11; E17; E52; 330; Climate change; Environmental policy; Optimal policy; Transition risk; Model uncertainty; DSGE models